The Martyrial Face of The Salvadorean Church from The Theological Biographies of Óscar Romero and Ignacio Ellacuría: A Revaluation of The Prophetic Dimension in The Ordained Ministry - Mauti, Ricardo Miguel (Institut Agama Kristen Negeri Toraja, 2024)
The purpose of this study is to present the relationship established between liberation and martyrdom in the Salvadorean Church. The angle of analysis is the theological biographies of Óscar Romero and Ignacio Ellacuría, both martyrs of El Salvador. The method of theological biography, in this case, allows theology not only to verify the announcement of the Kingdom as proposed by the Gospel of Jesus Christ, but also discovers a new contribution in the way of interpreting these nuclei of Christian revelation. Liberation and martyrdom are fundamental realities for liberation theology, and they endow it with a specific direction and pathos. Their commitment and denunciation of social injustice constitute a prophetic dimension that serves as a model for an entire local church and in particular for the ordained ministry. I am going to present my work with the formulation of three questions: the link between liberation and martyrdom (2), martyrs and the ordained ministry today (3), the problem of the Universal Church for a reception of the martyrs of justice (4), and some open conclusions.